My Creditor’s Keeper: Escalation of Commitment and Custodial Fiduciary Duties in the Vicinity of Insolvency - Amir N. Licht (Washington University Law Review, 2021)
Fiduciary duties in the vicinity of insolvency form a notoriously murky area where legal space warps. Courts openly acknowledge that it is difficult to identify its boundaries, and the content of these duties is equally uncertain and inconsistent across jurisdictions. This Article expands the theoretical basis for a special legal regime in virtually or liminally insolvent firms. In addition to the conventional rationale of opportunistic risk shifting, lawmakers should be mindful of managers’ tendency to unjustifiably continue failing projects, known as escalation of commitment. Second, this Article addresses the substantive content of a duty to protect creditors, either as in the form of a duty to consider creditors’ interest or as the statutory rule against wrongful (or insolvent, or reckless) trading. Specifically, it argues that when these duties are enlivened at the very edge of the zone of insolvency, the mission of directors should transform from entrepreneurial to custodial and should include a trustee-like duty of caution.
Keywords: Fiduciary duties; Corporate law; Corporate insolvency; Creditor protection; Vicinity of insolvency